2012
DOI: 10.1111/j.1540-8175.2011.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Echocardiography in Evaluation of Left Ventricular Indices

Abstract: Accurate determination of left ventricular mass, volume, ejection fraction, and wall motion is important for clinical decision making. Currently, M-mode and two-dimensional echocardiography (2DE) have been routinely used for this purpose. Although these 1D or 2D modalities provide excellent diagnostic and prognostic information, they have a number of technical limitations including the time required to perform the procedure and operator-dependent image acquisitions. In addition, they are inherently limited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…With the use of contrast agents these differences in volume measurement have reduced, however, this is still not to the level where results can be considered interchangeable. Regarding volumes 3D ECHO has been demonstrated to show a large improvement toward the values of CMR, and as such, is the most accurate ultrasound technique for determining LV function, although the total number of patients included in trials is still small and very good acoustic windows are needed . The most promising technique in echocardiography is certainly contrast 3D, however, the excellent results demonstrated by the Jenkins group in 2009 could not be reproduced by Caiani et al., and so further investigation is required .…”
Section: Discussionmentioning
confidence: 99%
“…With the use of contrast agents these differences in volume measurement have reduced, however, this is still not to the level where results can be considered interchangeable. Regarding volumes 3D ECHO has been demonstrated to show a large improvement toward the values of CMR, and as such, is the most accurate ultrasound technique for determining LV function, although the total number of patients included in trials is still small and very good acoustic windows are needed . The most promising technique in echocardiography is certainly contrast 3D, however, the excellent results demonstrated by the Jenkins group in 2009 could not be reproduced by Caiani et al., and so further investigation is required .…”
Section: Discussionmentioning
confidence: 99%
“…40 Finally, in previously reported studies, 3DE has shown to be a reproducible technique with optimal intra-and inter-observer variability. 3,41 Accordingly, studies included in the current work all had an optimal intra-and inter-observer variability. LV EF was the most reproducible parameter with excellent intra-and inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…The delineation of the right ventricle remains challenging for all imaging modalities because of its complex geometry and it will be of value to determine whether fusion can improve right ventricular assessment. 3D echocardiography has been known from most papers as an excellent LV assessment tool . However, there are also some views of limited usability for 3D .…”
Section: Discussionmentioning
confidence: 99%
“…3D echocardiography has been known from most papers as an excellent LV assessment tool. [28][29][30] However, there are also some views of limited usability for 3D. 31,32 A recent multicenter study suggested that contrast application may be needed with 3D echocardiography as 2D echocardiography to reduce inter-reader variability for volumes and ejection fraction.…”
Section: Discussionmentioning
confidence: 99%